DISTRIBUTION AND ABUNDANCE OF MAJOR ZOOPLANKTON GROUPS IN AMBON BAY (MALUKU, INDONESIA) DURING A SALP SWARMING, WITH NOTES ON CHAETOGNATHA AND PTEROPODA SPECIES - Troost, Dick G.; Sutomo, A. B.; Wenno, L. F. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1976)
Eight zooplankton samples from several stations along a line from the inner to the outermost part of Ambon Bay were studied. In the samples from the Inner Bay, the salp Thalia sibogae SOEST outnumbers all other groups. The competition for food is responsible for relatively low numbers of these groups. At the Outer Bay stations the Copepoda is by far the most abundant group.TGraphs indicating the numbers of specimens per m3 of each of the seventeen groups are given for three groups of stations, of which the central one appeared to be the richest.The Chaetognatha, Pteropoda, and oblong fish eggs were identified. Oxygen and reactive phosphorus are presumed to be more connected with differences in planktonic life in Ambon Bay than temperature and salinity.Because of the importance of the live-bait fishery, and the threat of increasing pollution, a call in made for more extensive surveys.